Developing Teacher Professionalism in Online Learning Through Assistance of Web-Based Digital Teaching Materials - Nurpratiwi, Suci; Amaliyah, Amaliyah; Hakam, Ahmad; Romli, Nada Arina (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2021)
This community service aims to develop teacher professionalism in online learning through assistance in preparing digital teaching materials. The methods used in the service activities are interactive lectures, discussions, practices, and assignments. The participants involved were 11 elementary school teachers. Community service activities are carried out through making guidelines, implementing assistance, monitoring, and assigning tasks. The service results show that the mentoring activities have succeeded in developing the abilities and professionalism of teachers in the use of technology in learning. Participants have compiled digital teaching materials independently and have implemented them for students in their online learning. Meanwhile, 81.82% of participants stated that service activities provided new insights, and 63.64% were satisfied with the activities carried out.Pengabdian kepada masyarakat ini bertujuan untuk mengembangkan profesionalisme guru dalam pembelajaran daring melalui pendampingan penyusunan bahan ajar digital. Metode yang digunakan dalam kegiatan pengabdian berupa ceramah interaktif, diskusi, praktik, dan penugasan. Peserta yang terlibat adalah guru Sekolah Dasar sebanyak 11 orang. Kegiatan pengabdian kepada masyarakat dilaksanakan melalui tahapan proses pembuatan panduan, pelaksanaan pendampingan, pemantauan, dan pemberian tugas. Hasil pengabdian menunjukkan bahwa kegiatan pendampingan berhasil mengembangkan kemampuan dan profesionalitas guru dalam penggunaan teknologi dalam pembelajaran. Peserta telah dapat menyusun bahan ajar digital secara mandiri dan telah mengimplementasikannya kepada peserta didik dalam pembelajaran daringnya. Adapun sebesar 81,82% peserta menyatakan kegiatan pengabdian memberikan wawasan baru, dan 63,64% peserta merasa puas dengan kegiatan yang telah dilaksanakan.